Primary School Administration in Nigeria: Issues, Problems and way Forward - Olowonefa, G. S. (International Journal on Integrated Education, 2022)
Primary school education is the foundation education and it is vital for the development of education in Nigeria. It is unfortunate that as important as the primary school education is to the social economic and technological advancement of the country that the education is faced with many issues and problems. This article discussed issues and problems facing primary school administration in Nigeria and the way forward. Secondary data were used to support the various points raised in the paper. The secondary school data were sourced from print materials and online publication. This paper identified insecurity, large out of school children and poor quality of learning as some of the issues affecting the administration of primary schools. The paper also identified inadequate funding, shortage of professional teachers, inadequate infrastructural facilities, ineffective supervision, corruption and lack of data to plan as problems militating against effective administration of primary schools in Nigeria. To solve these problems identified, the following were recommended; that the government should increase the funding of primary school education by implementing the UNESCO 26% recommendation for an annual budget of education in Nigeria. This will aid effective administration of primary school education in the country.